Desarrollo neo-extractivo en América del Sur. El dilema de las economías emergentes que puso en entredicho las democracias a comienzos del siglo XXI (Papeles, 2021)
The article deals with the consequences produced in the change of the financial model established by the Washington Consensus towards the acceptance of a new consensus based on the export of raw materials (commodities) on a large scale. The analysis focuses on the fact that the South American governments of the 2000s made the decision to reorient and prioritize their production towards primary–extractive or maquila activities. In other words, towards activities with low added value, the result of which is products generally destined for developed countries. This developmental extractivism has economic, social and political consequences. Regarding the economic ones, there is an effect of reprimarization of the Latin American countries; Socially speaking, this consensus leads to a dispossession and concentration of land and resources in the hands of corporations, implying an alliance between them and the different governments and, finally, democracy enters a delicate terrain facing mobilizations in defense of territory, biodiversity and the environment.
Keywords: new extravism; autonomy; development; environment